Cardenolides from Calotropis gigantea as potent inhibitors of hypoxia-inducible factor-1 transcriptional activity. (24th December 2016) - Parhira, Supawadee; Zhu, Guo-Yuan; Chen, Ming; Bai, Li-Ping; Jiang, Zhi-Hong
Abstract: Ethnopharmacological relevance: Calotropis gigantea (L.) Dryand (Apocynaceae) is a medicinal plant native to southern China, India and Southeast Asia. It has been traditionally used for the treatment of several diseases including cancers in these countries. Aim of the study: This study aimed to isolate bioactive cardenolides from C. gigantea, to screen their hypoxia-inducible factor (HIF-) 1 inhibitory activity, and to analyze the structure-activity relationship (SAR). Materials and methods: Isolation and purification of cardenolides from the latex and the fruits of C. gigantea were performed by using a series of separation techniques. Their structures were fully characterized by elucidating their NMR and HRMS data. The HIF-1 inhibitory activities of cardenolides were evaluated by using a T47D cell-based dual-luciferase reporter assay. The potent cardenolides were selected to further evaluate their dose-response manner. Cytotoxic effects of selected cardenolides were also examined against breast cancer cell line (MCF-7) and normal mammary epithelial cell line (MCF-10A) by MTT assay. Results: Among twenty isolated cardenolides, compounds1, 3, 4, 6–8, 14 and17 exhibited stronger HIF-1 inhibitory activities than that of digoxin, a well-known HIF-1 inhibitor ( P <0.001). These eight cardenolides inhibited HIF-1 transcriptional activity in a dose-dependent manner with IC50 values in nanomolar potency (21.8–64.9 nM). An analysis of SAR revealed the great contributions of a β -configuration of the substituents at positions of C-2′ and C-3′, an aldehydic moiety on C-19, and the dioxane moiety between the aglycone and sugar parts of cardenolides to the HIF-1 inhibitory activity. In contrast, a hydroxyl group at any positions of C-15, C-16 and C-4′ of cardenolides showed negative effects on suppressing HIF-1 transcriptional activity. In addition, these eight cardenolides also exhibited potent cytotoxic effects against human breast cancer cell MCF-7 (IC50 values ranged from 30.5 to 68.8 nM), but less toxic effects to human normal mammary epithelial cell MCF-10A (IC50 values >20 µM). Conclusions: This is the first report of a comprehensive study of SAR on cardenolides from C. gigantea as HIF-1 inhibitors. Eight cardenolides (1, 3, 4, 6–8, 14 and17 ) showed both potent HIF-1 inhibitory activity and strong cytotoxic effect against MCF-7 cancer cells in nanomolar level. The findings of these cardenolides provided important insights into the development of these potent HIF-1 inhibitors as anticancer drug. Graphical abstract: